Narrative Analysis of the Conclave (2024) Film - Louisa Christine Hartanto; Patrisia Amanda Pascarina; Imanuel Deni Krisna Aji; Jennifer Laurent; Yemima Elihu Virdiantoro (Journal of Feminism and Gender Studies, 2026)
The emergence of a new gender group categorized by the acronym LGBTQ+ in society has caused debate. The expressions they show in everyday life divide the opinions of various parties, one of which is the Catholic Church. This study aims to dissect the narrative in the film "Conclave" (2024) which shows the conflicting views of the bishops when choosing a new Pope in the Conclave session. The conflict between conservative and liberal bishops leads them to the fact that the elected Pope turns out to have a condition called intersex. In order to dissect the confession of the Catholic Church in the film, this study uses Todorov's narrative analysis method which states that the complexity of a narrative is structured based on the level of story and level of plot. Although this film does not directly tell that the bishops participating in the conclave accept the LGBTQ+ group as members of the church, at the end of the film it is shown that a person's identity is a blessing from God and humans have no right to change. This film emphasizes the paradigm of forgiveness, that although the Church does not justify or blame the existence of the LGBTQ+ group, they still prioritize God's love which is expressed in the Sacrament of Forgiveness of Sins. The results of this study will add to the discussion on the existence of LGBTQ+ groups in society as reflected in popular media representations and how the public forms perceptions of these groups.